Bank syariah: peran sosial dalam kerangka maqashid syariah dan profitabilitas di negara Qatar dan Indonesia - Kartika Sari (Journal of Business & Banking, 2019)
This research aims to determine the role of social Islamic bank and the Islamic bank's business objectives are gaining profit. Islamic banks are tied to sharia principles and carry on social roles in the concept of Sharia Maqashid in conducting its business.The social role is to carry out social values such as education, justice and social welfare. The method used to determine the social role of Sharia banks is by measuring Maqashid Index Syariah Index (MSI) while the profitability is known using the comparative Performance index method on seven Islamic banks spread across The country of Qatar and Indonesia in 2010-2017.To know both social roles and profitability using Quadrant Analysis Measurememnt (QAM).The results showed that of the seven Islamic banks spread across the country of Qatar and Indonesia, Only three Islamic banks are good for the profitability of the Bank, there are Qatar International Islamic Bank, Qatar Islamic Bank and Bank Syariah and Mandiri. But the achievement of the social role of the three Islamic banks is not good so that in the the Upper Left Quadrant (ULQ). Meanwhile, four other sharia namely Barwa, Bank Muamalat Indonesia, Syariah National Bank and Bank Rakyat Indonesia Syariah do not well achieve the social role and profitability so that in the Lower Left Quadrant (LLQ).